Implementation Barriers in Literacy and Numeracy Drive (LND) in NFBEIs: Teachers’ Perspective - Zahra, Nausheen (IJLTP, 2025)
Technological revolutions demand that educational institutions change towards technology-oriented teaching and assessment. NFBEIs are designed to improve the literacy rate. These educational institutes help to develop social, cognitive, cultural and higher-order skills in individuals using various learner-centered approaches while teaching and learning. Literacy and Numeracy Drive is an innovative initiative to impart education and skills through technology. Present research investigated “Implementation Barriers in Literacy and Numeracy Drive (LND) in NFBEIs: Teachers’ Perspective”. The population comprised of 100 schools from non-formal basic Education Institutes (NFBEIs) of Tehsil Chakwal. A randomly selected sample of 21 schools was part of this study. A self-developed closed-ended questionnaire was developed to collect data from teachers of 21 schools on a 5-point Likert scale. Data were collected through personal contact by obtaining informed consent from teachers and school authorities. Descriptive (mean and percentage) and one-sample independent t-test were used for data analysis. The findings revealed that teachers faced many technological challenges while implementing LND, which included a lack of technological devices, availability of internet connection, technological awareness among parents, and more technological issues in rural areas. This study recommends that the availability of digital devices, internet connection, LND applications, teacher training, and community involvement is essential for the effective implementation of LND in NFBEIs.